Hydraulic jump in non-prismatic rectangular sloping channels - Chen, Chia-feng; Wang, Tsan-Wen; Gupta, Ashim Das; Prida Thimakorn; Ret-Ser Engineering Agency . R.o.c. (Bangkok : Asian Institute of Technology, 1986)
A study of the hydraulic jump occuring within the testing zone of a gradually expanding rectangular tilting channel is presented. This expanding channel jump is considered to behave as a segment of a circular jump. The equations describing the characteristics of expanding rectangular channel jump are derived from three basic principles of fluid mechanics. The observations were conducted by varying the bed slope of flume from -0.05 to +0.05 with an increment of 0.005 as sluice gate opened at 2 cm. Experimental results are shown in graphic form and drawed by best fit on experimental points. The experimental data support the theoretical analysis. The equation developed for jump with proper evaluation of the effects of side pressure and body pressure forces, describes well the jump in a gradually expanding rectangular channel with slopes. It was also concluded that the expanding channel jump in sustaining slopes is better than that in adverse slopes for energy dissipation.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Hydraulic jump; Channels (Hydraulic engineering)